Cardiovascular Risk Factors Are Correlated with Low Cognitive Function among Older Adults Across Europe Based on The SHARE Database - Lourenco, J (2018)
Increased life expectancy is associated with a high prevalence of chronic, non-communicable diseases including cognitive decline and dementia. The purpose of this study was to evaluate the prevalence of cognitive impairment using three cognitive abilities (verbal fluency, numeracy and perceived memory) and their association with cardiovascular risk factors in seniors across Europe. Data from participants in wave 4 of the SHARE (Survey of Health, Ageing, and Retirement in Europe) database was used. Cognitive performance in perceived memory, verbal fluency and numeracy was evaluated using simple tests and a memory complaints questionnaire. Clinical and sociodemographic variables were also studied for potential associations. Standardised prevalence rates of cognitive impairment based on age and gender were calculated by country. The prevalence of cognitive impairment was 28.02% for perceived memory, 27.89% for verbal fluency and 20.75% for numeracy throughout the 16 evaluated countries. Years of education, being a current or former smoker, number of chronic diseases, diabetes or hyperglycemia, heart attack and stroke were all independent variables associated with impairment in the three studied cognitive abilities. We also found independent associations between physical inactivity and verbal fluency and numeracy impairment, as well as hypertension and perceived memory impairment. Lower performance in the evaluated cognitive abilities and higher memory complaints are highly prevalent, have a heterogeneous distribution across Europe, and are associated with multiple factors, most of which are potentially preventable or treatable, especially cardiovascular risk factors.